Preparation of construction of preinsulated district heating networks in PE-HD casing laid directly in the ground. Part III - Kręcielewska, Ewa; Starobrat, Artur; Iwko, Ireneusz (Instal, 2025)
A high quality of the investment related to the construction and subsequent operation of district heating pipelines is ensured by performing it on the basis of properly developed project documentation, which:‒ should contain all the information required for roper execution of the works,‒  be sufficiently detailed to ensure that the construction project can be carried out in accordance with the assumed and expected quality. After the investment is completed, detailed post-construction documentation should be prepared. The article describes the necessary work and its scope, enabling the preparation of correct design documentation for a pre-insulated heating network.
Keywords: preinsulated district heating networks; design documentation